CONJECTURES AROUND THE COMPARATIVE EDUCATION - Elvia Marveya Villalobos; Trejo Sánchez (European Scientific Journal, ESJ, 2014)
The central premises and objectives that encourage this proposal to reflect around the conjectures of comparative education (CE) are specific, in first place, by the need applies even in the current record CHANGE and their implications for public policies on education, accelerate changes, with more emphasis in the first decade of the twenty-first century, where the prudency requires the constant prevalence of the Comparative Education by the decisions takers in every education systems recognizing that is required to ADAPT and not only to adopt the <> of the International organisms, in an era where the knowledge has been globalized. Every change needs in advance an analysis of CE. In second place, the requirement to adapt in a harmonic form the changes in the precise context of the <> based in each and every one of the constitutive elements of every education system. Inasmuch as, the <> is the same in the whole world because there will always be a teacher, students and educational content, while the <> is the educational fact plus its economic, politic and social context that makes it unique and unrepeatable. In third place, is necessary to recognize that today‘s CE first of all is a METHODOLOGICAL ALTERNATIVE to perform educational innovation, reform or revolution changes as well as the adaptions that actual social reality imposes. In this context there are many and varied conjectures that epistemological and methodologically involves the CE development.